A review on biotechnological potential of multifarious enzymes in bread making. (December 2020) - Dahiya, Seema; Bajaj, Bijender Kumar; Kumar, Anil; Tiwari, Santosh Kumar; Singh, Bijender
Highlights: Addition of exogenous enzymes enhances the activity of endogenous flour enzymes. Supplementation of microbial enzymes replaces the use of chemical additives in foods. Microbial enzymes can show their effects alone and in combination with other enzymes. Mineral bioavailability and digestibility of bread improved by phytases. Shelf-life of bread extended by addition of xylanases, glucose oxidases, and amylases. Abstract: Baking is a universal process for the preparation of baked products like, bread, biscuits, pastries, cookies, crackers, pies, and others. Although usage of enzymes in bakery is quite old but recent developments in basic biology, biochemistry, advancements in technological approaches, and discovery of new/novel enzymes, has revolutionized the application potential of enzymes in a variety of food industries including the bakery. World over people want their foods to be free of chemical preservatives and additives, therefore, the role of enzymes in potentially replacing the chemicals is very imperative. Application of enzymes in bakery not only enhances the dough properties such as, gas retention, crumb softness, water absorption capacity, and others but improves the nutritional status of products. Microbial sources of enzymes offer multiple advantages over plants and animals. Microbial enzymes from diverse resources have been reported for usage in bread making. A wide array of microbial enzymes viz. xylanases, phytases, α-amylases, proteases, cellulases, glucose oxidases, lipase and others have been reported to enhance the nutritional, sensory and other desirable properties of bread. Current article presents recent developments on application of enzymes for improvement of bread quality.